Chronic exercise activity and the fatigued athlete myopathic syndrome (FAMS) - Gibson, A. S.; Lambert, M. I.; Collins, M.; Grobler, L.; Sharwood, K. A.; Derman, W. E.; Noakes, T. D. (International SportMed Journal, 2000)
There is recent evidence to suggest that long-term endurance training of high mileage may result in cumulative, irreversible muscle damage. This muscle damage includes poor organization of muscle fascicles, abundant connective tissue, increased internal nuclei, changes in cytoskeletal muscle proteins and, in particular, mitochondrial pathology. The fatigued athlete myopathic syndrome (FAMS) describes athletes who present with chronic fatigue and evidence of these muscle abnormalities. The symptoms of FAMS vary, but the common features of athletes with this syndrome are (i) a history of high-volume training for many years, who present with decreased exercise performance and a clinical picture dominated by skeletal muscle symptoms, and (ii) a history of consulting many clinicians unsuccessfully. It is still not clear how the muscle pathology relates to the symptoms of fatigue in FAMS individuals. Theories include (i) chronically activated afferent nerve fibers from chemoreceptors, golgi tendons, or nociceptors in the damaged muscles; (ii) changes in the hypothalamic-pituitary-adrenal axis impinging on cortical or midbrain structures; (iii) changes in brain structures themselves either as a result of, or unrelated to, the muscle damage; and (iv) the symptoms of fatigue may be part of a clinical depression in the FAMS individual due to the affect on his/her lifestyle or psychological makeup of the deterioration in their athletic performance. Further work is required to isolate which of these causes is responsible for the onset of FAMS in susceptible, exercising individuals.